The Effect Of Green Advertising And Green Product On Green Purchase Intention With Green Trust As Mediation Variable On Consumers Of Water Packaging "Ades" In Surabaya - Sandy Teguh Abdillah; Ignatia Martha H (Jurnal Mantik, 2022)
Ades is one of the products launched by Coca Cola Amatil Indonesia (CCAI) which implements Green Advertising. This study aimed to determine the influence of Green Advertising and Green Product towards Green Purchase Intention with Green Trust as mediation variable on consumers of water packaging Ades in Surabaya. This research use explanatory research with a quantitative approach, and instrument of this research is using questionnaire. The sample used is 130 respondents who are minimum 17 years old, domiciled in Rungkut District Surabaya, and are consumers of water packaging by ades brand.instrument validity test using Product Momment Pearson, and the realibility test using Alpha Cronbach. Partial Least Square analysis is used to test the hypothesis of this research. The results show that (1) Green Advertising do not have a strong influence to Green Trust on ADES consumers, (2) Green Products have a strong influence to Green Trust on ADES consumers, (3) Green Advertising do not have a strong influence to Green Purchase Intention on ADES consumers, (4) Green Products do not have a strong influence to Green Purchase Intention on ADES consumers, and (5) Green Trust have a strong influence to Green Purchase Intention on ADES consumers.